1996
DOI: 10.1021/la9515480
|View full text |Cite
|
Sign up to set email alerts
|

Potential-Step Chronocoulometric Investigation of the Surface Coverages of Coadsorbed Bi and Hydroxide on Au(111) Electrodes

Abstract: Bi underpotentially deposited on Au(111) has been studied using potential-step chronocoulometry to determine the actual surface coverage of Bi. In the potential region where this system exhibits catalytic activity for the electroreduction of peroxide to water, the observed coverage is 0.25 monolayer (ML), which agrees well with the coverage of the reported (2 × 2) Bi overlayer observed by scanning probe microscopy in this region. At more cathodic potentials, the coverage increases to 0.67 ML. This coverage agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 30 publications
5
49
0
1
Order By: Relevance
“…The enrichment of the surface with Bi 0 is explained by the leaching of the Bi 2 O 3 surface species and redeposition of Bi 0 on platinum in the upd region. Gewirth group [59,60] studied Bi-modified Au surfaces using notably electrochemical and surface-enhanced Raman spectroscopy (SERS) methods. They showed that Bi-OH and Bi-O species are formed in the catalytically active region and that OH À is coadsorbed with the Bi in the upd region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enrichment of the surface with Bi 0 is explained by the leaching of the Bi 2 O 3 surface species and redeposition of Bi 0 on platinum in the upd region. Gewirth group [59,60] studied Bi-modified Au surfaces using notably electrochemical and surface-enhanced Raman spectroscopy (SERS) methods. They showed that Bi-OH and Bi-O species are formed in the catalytically active region and that OH À is coadsorbed with the Bi in the upd region.…”
Section: Discussionmentioning
confidence: 99%
“…The leaching and redeposition of Bi species can lead to the surface segregation of Bi, covering most of the surface. Niece and Gewirth [59] showed that on Au (1 1 1), Bi adsorb in multiple steps with only partial coverage in the catalytically active region. However, redeposition of Bi on platinum surface can lead to the increase of the coverage and to a modest increase of the reaction rate by lowering the number of adjacent actives sites for the dissociative adsorption of EG [61].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its unique physical and chemical properties, bismuth has been attracting many interests from physicists and chemists. Up to now, most of the studies involving electrochemistry and bismuth can be divided into five classes: (a) a promising electrochromic material [1,2], (b) electrocatalytic activity of bismuth monolayer/ sub-monolayer (underpotential deposition of bismuth) on some noble metal surfaces, as well as the effect of bismuth adatoms [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], (c) an attractive alternative to the traditionally used mercury film electrode in electroanalysis [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], (d) correlations between the morphologies and sizes of metallic bismuth with large magnetoresistance [37][38][39] or thermoelectric efficiency [40], and (e) overpotential deposition of bismuth onto several electrode materials [2,[41][42][43]…”
Section: Introductionmentioning
confidence: 99%
“…1 shows a cyclic voltammogram run at 10 mV s À1 using a Au(1 1 1) single crystal electrode (area = 0.180 cm 2 ) in a solution consisting of 0.1 M HClO 4 and 1 mM Bi 3+ recorded between +0.5 and À0.5 V. On the forward sweep a range of peaks is observed between +0.35 and +0.05 V which correspond to the underpotential deposition (UPD) of bismuth on Au(1 1 1) the features of which are discussed in detail in Refs. [10,11,16,27]. Three phases have been identified in the Bi UPD region.…”
Section: Resultsmentioning
confidence: 98%
“…The UPD and OPD have different structures and will have different mechanisms for deposition. The atomic structures of Bi UPD phases at well-defined surfaces such as Au(1 1 1) have been determined using in situ STM, AFM and surface X-ray scattering [10][11][12] and electrochemical methods have been used to evaluate Bi coverage and characterize this adsorption process [13][14][15][16][17][18]. However, the growth mechanisms for the bulk deposition of bismuth are not well understood.…”
Section: Introductionmentioning
confidence: 99%